The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1016/s2213-2600(19)30086-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Russian-backbone live-attenuated influenza vaccine with an updated pandemic H1N1 strain on shedding and immunogenicity among children in The Gambia: an open-label, observational, phase 4 study

Abstract: Background The efficacy and effectiveness of the pandemic H1N1 (pH1N1) component in live attenuated influenza vaccine (LAIV) is poor. The reasons for this paucity are unclear but could be due to impaired replicative fitness of pH1N1 A/California/07/2009-like (Cal09) strains. We assessed whether an updated pH1N1 strain in the Russianbackbone trivalent LAIV resulted in greater shedding and immunogenicity compared with LAIV with Cal09. Methods We did an open-label, prospective, observational, phase 4 study in Suk… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
39
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 24 publications
3
39
1
Order By: Relevance
“…Only 16 (14%) of 118 who received the CA/09 LAIV shed the H1N1 vaccine virus and 6 (5%) seroconverted, whereas 80 (63%) of 126 who received the NY15 LAIV shed vaccine virus and 24 (19%) seroconverted. The NY15 strain also induced more robust T-cell immunity than CA/09 (Lindsey et al 2019). These data are consistent with the improved shedding indicative of replicative fitness with the U.S.-backbone LAIV containing A/Slovenia/2015 in place of CA/09 and suggest that the poor VE with the Russian-backbone LAIV observed in Senegal may be overcome with a different vaccine strain.…”
Section: Experience With Russian-backbone Laivsupporting
confidence: 76%
“…Only 16 (14%) of 118 who received the CA/09 LAIV shed the H1N1 vaccine virus and 6 (5%) seroconverted, whereas 80 (63%) of 126 who received the NY15 LAIV shed vaccine virus and 24 (19%) seroconverted. The NY15 strain also induced more robust T-cell immunity than CA/09 (Lindsey et al 2019). These data are consistent with the improved shedding indicative of replicative fitness with the U.S.-backbone LAIV containing A/Slovenia/2015 in place of CA/09 and suggest that the poor VE with the Russian-backbone LAIV observed in Senegal may be overcome with a different vaccine strain.…”
Section: Experience With Russian-backbone Laivsupporting
confidence: 76%
“…In addition, prior serostatus has no impact on the likelihood of a 2-fold mucosal IgA response. This is in keeping with our findings that shedding increases the odds of seroconversion and a T-cell response, but not mucosal IgA responses[2]. Furthermore, ~50% of children generated a T-cell response to A/HK Haemagglutinin despite being A/HK seropositive, challenging the view that giving LAIV may not be worthwhile in the face of pre-existing serum antibody immunity to vaccine strains.…”
supporting
confidence: 82%
“…The proposed model assumes that pre-existing serum antibodies from prior infection or vaccination are the main driver of LAIV 'take' and immunogenicity. Our own data using Russian-backbone LAIV in Gambian children aged 24-59 months partially support this, with pre-immunization serum haemagglutination inhibition (HAI) titre (but not T-cell response or mucosal IgA) being the key determinant of LAIV shedding [2]. We have recently stratified this cohort based on seropositivity to the H3N2 strain included in the vaccine (A/Hong Kong/4801/2014; A/HK), and two older H3N2 strains antigenically similar to those potentially encountered during the children's lifetime (A/Switzerland/9715293/2013; A/Sw or A/Texas/50/2012; A/Tex).…”
mentioning
confidence: 67%
“…LAIV is preferentially recommended for use in children, but the recommendation was withdrawn in the US because seasonal LAIV was not effective against H1N1pdm09, although no single cause for this failure was identified (13). However, recent studies showed that switching the H1N1 component might overcome the poor effectiveness reported with previous LAIV formulations (14).…”
Section: Introductionmentioning
confidence: 99%